DATA PROTECTION AGAINST MALWARE USING MACHINE LEARNING TECHNIQUES - Shoraimov Husanboy Uktamboyevich; Tashpulatova Nadira Botirovna; Akbarova Marguba Xamidovna (International Engineering Journal For Research & Development, 2022)
Cyber attacks on confidential data have become a serious threat around the world due to the growing use of computers and information technology. Cyber criminals daily release new malware or viruses over the Internet in an attempt to destroy or steal sensitive data. Consequently, data protection research is of great interest in the Cyber community, to deal with new malware variants, machine learning techniques can be used to accurately classify and detect. This article proposes an efficient scheme for detecting malicious threats using data mining and machine learning methods. Experimental results show that the proposed approach gives better performance compared to other similar methods.